QUANTUM LEAP: WHEN COMPUTERS TRANSCEND THE LIMITS OF CLASSICAL LOGIC - Muhammad Yusuf; Rusnai Rahayu; Endang Pratiwi; Nur Hajjeni; Adinda Luminto (TECHSI - Jurnal Teknik Informatika, 2025)
The rapid evolution of information technology has entered a new phase that increasingly challenges the limits of classical computational logic. Quantum computing has emerged as a new computational paradigm that exploits the principles of quantum mechanics to address problems that are computationally infeasible for conventional computers. This study aims to analyze the fundamental concepts of quantum computing, recent technological developments, and its potential implications for the field of information technology. A Systematic Literature Review (SLR) method was employed by analyzing peer-reviewed journal articles and research reports published between 2019 and 2025. The results indicate that quantum computing demonstrates significant potential in areas such as cybersecurity, artificial intelligence, and big data analytics. However, critical challenges remain, including qubit instability, decoherence, quantum error correction, and high implementation costs. This study concludes that quantum computing represents a transformative technological leap that is expected to reshape the future trajectory of global information technology, provided that existing technical and infrastructural challenges can be effectively addressed.